The relationship between the moving class model, pedagogical competence, student learning motivation, and learning discipline in geography learning - Mohammad Amin Lasaiba; Irvan Lasaiba; Arman Man Arfa; Djamila Lasaiba (Jurnal Penelitian Ilmu Pendidikan, 2024)
The tendency in geography education remains to use teacher-centered approaches, placing emphasis solely on cognitive aspects, and it has yet to fully leverage students’ learning motivation. Through the moving class model, it becomes possible to actively and creatively engage students while fostering their discipline in learning. The urgency of this research lies in developing an effective educational system and its significant contribution to addressing present-day educational challenges. This study aims to describe the interaction among innovative learning models, teachers’ pedagogical competence, student learning motivation, and learning discipline. A quantitative explanatory approach was adopted, with the population comprising all tenth-grade students at SMAN Ambon (288 students across seven classes). Samples were selected through simple random sampling by class, resulting in two groups: an experimental class with 41 students and a control class with 40 students. Data were collected via Likert-scale questionnaires, observations, and documentation. For data analysis, Structural Equation Modeling (SEM) was employed, consisting of four key steps: designing the inner model and outer model, evaluating goodness of fit, hypothesis testing, and interpretation. The results highlight the importance of the Moving Class Model and teachers’ pedagogical competence in influencing students’ learning motivation and learning discipline. These findings support the idea that interventions aimed at enhancing learning quality through dynamic learning model implementation and improving teachers’ pedagogical skills can positively impact students’ motivation, which in turn affects their learning discipline. The implications underscore the importance of these factors in supporting optimal achievement in the learning context and the need to strengthen them to improve educational quality. Recommendations stemming from this research emphasize the need for closer integration of innovative learning models, enhancement of teachers’ pedagogical competence, and the development of a conducive learning environment.